2019
DOI: 10.1111/echo.14453
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular dyssynchrony in coronary artery disease patients without regional wall‐motion abnormality: Correlation with Gensini score

Abstract: Objectives Our study investigated left ventricular dyssynchrony (LVD) in coronary artery disease (CAD) patients without regional wall‐motion abnormality (RWMA) by three‐dimensional echocardiography (3‐DE) and explored the relationship between LVD and severity of CAD as assessed by the Gensini score (GS). Methods Sixty‐one patients with a confirmed diagnosis of CAD by coronary angiography (CAG) were enrolled. We quantified LVD parameters, including the left ventricular segments (16, 12, and 6) standard deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Another study used 3-dimensional echocardiography to quantify LVMD in CAD patients without regional wall motion abnormality and found out that CAD patients still demonstrated increased LVMD compared with healthy controls. 10 Logistic regression analysis of this study showed that significant predictors of LVMD were myocardial ischemia, infarction scar extent and QRS duration. In additional analysis, when EF was included in the model, significant predictors of LVMD were male sex, ischemia, larger end-diastolic volume, low ejection fraction and longer QRS duration, but not infarct scar extent.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Another study used 3-dimensional echocardiography to quantify LVMD in CAD patients without regional wall motion abnormality and found out that CAD patients still demonstrated increased LVMD compared with healthy controls. 10 Logistic regression analysis of this study showed that significant predictors of LVMD were myocardial ischemia, infarction scar extent and QRS duration. In additional analysis, when EF was included in the model, significant predictors of LVMD were male sex, ischemia, larger end-diastolic volume, low ejection fraction and longer QRS duration, but not infarct scar extent.…”
Section: Discussionmentioning
confidence: 62%
“…Another study used 3-dimensional echocardiography to quantify LVMD in CAD patients without regional wall motion abnormality and found out that CAD patients still demonstrated increased LVMD compared with healthy controls. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, many studies explored the methods of predicting and evaluating the lesions, mainly including the determination of many biomarkers such as vascular-related inflammatory factors, growth differentiation factors, and angiopoietin-like proteins in the body, and imaging techniques such as coronary angiography [ 8 , 9 , 10 ]. However, there are some disadvantages such as high cost and trauma to the body of these methods [ 11 ]. Therefore, it is of great clinical significance to find a simple, noninvasive, convenient, economic, and repeatable detection index for an early and accurate evaluation of the degree of lesions to prevent senile CHD.…”
Section: Introductionmentioning
confidence: 99%
“…LVD may have higher predictive value for events compared to electrical dyssynchrony. In the article by Li M et al, the LVD as assessed by 3‐Dimensional echocardiography (3DE) correlated well with Gensini score in patients with CAD but without regional wall‐motion abnormalities. Gated single photon emission computerized tomography myocardial perfusion imaging (SPECT‐MPI) also has shown similar correlation of LVD with the severity of CAD .…”
mentioning
confidence: 97%